Review Article: John and the Jews - Edwards, Ruth (The expository times, 2002)
At least in retrospect, Good Friday and Easter represent the critical point of separation between Judaism and the new Christian faith. For some time it was not evident that the divorce was total, but in time it was effected completely. The parting of the ways was not without its pain, and the pain has left its mark on both faiths. The story of Christendom is marred by conflict and anti-Jewish prejudice, which needs to be viewed in a spirit of repentance. What is slower to dawn on some of us, not least in the pulpit, is that the use of biblical references to 'the Jews' may unwittingly perpetuate prejudicial language. For too long references to the Pharisees, for example, as arid legalists have presented caricatures of the historical reality, and the suggestion that 'the Jews' were responsible for Jesus' death perpetuates one of the worst forms of prejudice. More recently, attention has been paid to the problem of such language in the New Testament and in the Fourth Gospel in particular. In the following review article, Ruth Edwards discusses an important contribution to the debate.